UJI TIGA GENOTIPE CABAI MERAH (Capsicum annuum L.) PADA FORMULASI PUPUK DI LAHAN GAMBUT - Arief ' Wibowo; Armaini ' '; Wardati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to obtain the superior genotypes of chili (Capsicum annuum L.) that give respons to fertilizer, able to grow and adapted so well, then produce  high  quality  of  yield  at  peat  land.  The  research  was  conducted  by experiment method. The experiment used Split Plot Design contained 3 times of repetition  and  2  times  formulation  of  fertilizer  that  consisted  formulation  of fertilizer I (Urea 600 kg/ha, TSP 500 kg/ha, KCl 400 kg/ha, organic fertilizer 10 ton/ha) and formulation of fertilizer II (NPK 700 kg/ha where organic fertilizer 15 ton/ha) as principal plot and 3 genotypes (IPB C-120 x IPB C-5, IPB C-2 x IPB C-120  and  IPB  C-5  x  IPB  C-120)  as  subplot.  The  variables  observed  were diameter of stem, high of  dichotomous, wide of branches, age of blooming, the diameter, length, and weight of fruit  respectively and the weight of fruits per plant. The result showed that superior genotypes and formulation of fertilizer in genotypes 3 (IPB C- 5 x IPB C-120) with the formulation of fertilizer II, it was NPK 700 kg/ha and organic fertilizer 15 ton/ha.   Keyword : Genotypes of chili, formulation of fertilizer, peatland.